Neurotropic T‐cell lymphocytosis: a cutaneous expression of CLIPPERS. (21st May 2014) - Smith, Annika; Matthews, Yasmin; Kossard, Steven; Turner, Jenny; Buckland, Michael E.; Parratt, John
<x xml:space="preserve">Abstract</x> Chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids (CLIPPERS) is an inflammatory disease of the central nervous system that predominantly involves the pons and cerebellum and that improves with immunosuppressive treatment. Only recently described, the etiology is unknown, diagnosis is difficult and long‐term neurological sequelae may occur without aggressive treatment. Herein, we describe a 59‐year‐old woman who presented with subcutaneous nodules affecting her face, trunk, limbs and an indurated annular erythematous lesion on her forearm. This was associated with marked dysesthesia of her skin, refractory to treatment. There was a 4‐year history of dysequilibrium, vertigo, truncal and gait ataxia with progressive neurological symptoms. Skin biopsy of the annular nodular lesion showed a lymphohistiocytic infiltrate in dermis and subcutis with a striking lymphocyte‐dominant infiltrate that was perineural and formed a nodular collection extending along a prominent subcutaneous nerve. Immunophenotyping indicated a marked predominance of T cells that were CD3 positive with a 2 : 1 CD4 : CD8 ratio. Scattered histiocytes were present but no well‐formed granulomas or vasculitis. Magnetic resonance imaging studies showed changes in the pontine, brain stem and cerebellar region, which subsequently were defined as characteristic for CLIPPERS, but no brain biopsy was pursued. The marked neural skin symptoms and the cutaneous histopathological findings indicate that the skin may be an additional target organ in CLIPPERS, and the immune response may be directed against a common neural antigen. In radiologically typical CLIPPERS, identification of clinical skin lesions particularly subcutaneous nodules and biopsy may potentially form a basis for tissue diagnosis in this syndrome.